Modeling of Subsurface Biobarrier Formation - Benito Chen-Charpentier; Hristo Kojouharov (Journal of Hazardous Substance Research, 2001)
Biofilm-forming microbes can form biobarriers to inhibit contaminant migration in groundwater and potentially biotransform organic contaminants to less harmful forms. Biofilm-forming microbes thereby provide an in situ method for treatment of contaminated groundwater. A mathematical and numerical model to describe the population distribution and growth of bacteria in porous media is presented here. The model is based on the convection-dispersion equation with nonlinear reaction terms. Accurate numerical simulations are crucial to the development of contaminant remediation strategies. We use the nonstandard numerical approach that is based on non-local treatment of nonlinear reactions and modified characteristic derivatives. This approach leads to significant qualitative improvements in the behavior of the numerical solution. Numerical results for a simple biobarrier formation model are presented to demonstrate the performance of the proposed new method. Comparisons of simulated results with experimental results obtained from the Montana State Center for Biofilm Engineering are also presented.
Keywords: biobarriers; models; biofilms; simulations